Evaluation of TOPS score as predictor for outcome in sick newborns - Sheth, Nirali Maheshbhai; Pandya, Nimisha (International Journal of Contemporary Pediatrics, 2020)
Background: Multiple parameters have been developed to prognosticate the outcomes of critically ill newborns admitted in NICUs. The objective of this study is to predict the outcome of newborns admitted in NICU using a simple but efficient score, TOPS score, involving alteration of physiological parameters. Aim of this study was to evaluate role of TOPS score in predicting mortality in sick neonates. Methods: The variables assessed under TOPS score on arrival for all subjects were: Temperature, Oxygen Saturation, Perfusion and blood glucose reading <45 mg/dl. All affected neonates were given treatment as per NICU protocol and outcome was assessed in terms of mortality or discharge using TOPS score. It was prospective study conducted at NICU, Department of Pediatrics, GMERS medical college and general hospital, Gotri, Vadodara. Study population was all admitted neonates aged <28 days at NICU. Results: Mean age of presentation of all cases was 2.8±3.58 days. Hypothermia on admission was observed in 63.3% cases. 40.8% cases had hypoxia. 26.5% neonates recorded poor perfusion. Mortality observed in hypoxic group was 51.7% followed by hypothermic group (46.9%). Highest strength of association was found for poor perfusion, mortality (87.5%) and OR-33.406. TOPS score was observed to be statistically significant (X2 value is 63.27, p < 0.05) as predictor of mortality. Thus, mortality rate increased with increasing no. of altered TOPS parameters. Regression analysis showed three factors (hypothermia, hypoxia, prolonged CRT) which are consistently associated with p value ≤ 0.05 for each variable and can be used to predict mortality. Conclusions: All parameters in TOPS score are physiologically important and each parameter carries an independent risk associated with mortality. It is important to note that multiple parameters affected increases the risk. TOPS score is a simple, basic and effective tool to guide about the condition of new born at admission and outcome. of neonatal mortality.